Islamic Education and The Challenges of Spirituality Crisis in The Age of Social Media - Ardilla, Verawati (Jurnal Ilmiah Teunuleh, 2024)
The rise of social media has profoundly transformed how people interact, communicate, and construct their identities. However, this advancement has also triggered a spiritual crisis characterized by the weakening of religious awareness, increasing consumerism, and a materialistic orientation toward life. The rapid rise of social media has fundamentally reshaped human identity and triggered a contemporary spiritual crisis marked by increasing consumerism, moral decay, and fragmentation of religious consciousness. Using a library research method, this study examines relevant literature on Islamic education, social media, and modern spirituality. This article critically analyzes the challenges and opportunities for Islamic education in responding to this crisis. Drawing on literature, the study identifies that while Islamic education faces threats like moral degradation and spiritual alienation, social media offers strategic platforms for value-based da'wah.  Nevertheless, social media also provides strategic opportunities for Islamic education to serve as a platform for da'wah and value-based character formation. This paper argues that the spiritual crisis is conceptually linked to Zygmunt Bauman's theory of Liquid Modernity and proposes a reorientation model focusing on transformative pedagogy (from transfer of knowledge to tarbiyah ruhiyah). Integrating critical digital literacy, media ethics, and spiritual consciousness is essential to foster the insan kamil identity amidst digital complexity.